Women and Crime: The Relationship Between Women and Organized Crime in Turkey - Furkan YILDIZ (Alınteri sosyal bilimler dergisi, 2019)
During the first existence of criminology which focuses on crime and criminals, detailed research has been carried on the issue of female offenders. This study evaluates the female criminality under the light of criminology and from the perspective of gender issue. In this respect, it has evaluated the case studies which are about the female leadership in organized crime in Turkey. In this study, both newspaper articles from 2008 to 2018 about female leadership in organized crime and increasing female criminality has been assessed from the eyes of criminology. As a result of these evaluations, women are not only victims in the most of the crimes but also offenders. In these offences, they commit crimes against women or use other women a tool for their crimes. Women are not the key actors in crime like men but women become as key actor in such crimes prostitution, theft, qualified form of fraud and counterfeiting. This study examines women’ role in crime business as a contribution to the literature instead it evaluates their tendencies under only gender issue.